CORPORATE IMAGE, RECRUITMENT IMAGE AND INITIAL JOB CHOICE DECISIONS. - Gatewood, R. D.; Gowan, M. A.; Lautenschlager, G. J. (Academy of Management Journal, 1993)
Aspects of corporate image, or the image associated with the name of an organization, and recruitment image–the image associated with its recruitment message–were studied. Data collected from fiv...